2022
DOI: 10.31234/osf.io/t6fkg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event segmentation in continuous, naturalistic videos from model-based, data-driven, and human perspectives

Abstract: Human experience is characterised by an apparently continuous stream of information. However, when recalling our past, we commonly experience somewhat discrete episodes. Event segmentation has been suggested to provide a basis for episodic memory formation and recognition/recall. Previous work has suggested that event boundaries are reflected in shifts in stable patterns of neural activity across processing hierarchies, and that these boundaries can be detected using neuroimaging techniques. From a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…It has previously been hypothesized that neural states should reflect meaningful units in the environment (Baldassano et al, 2017). However up to now, neural state boundaries have only been linked to event boundaries specifically (Baldassano et al, 2017; Geerligs et al, 2022; Mariola et al, 2022) and it has not been investigated if neural states at different levels of the temporal hierarchy indeed represent different meaningful units. In line with this hypothesis, we found that there is a significant alignment between changes in location and neural state boundaries in the place-sensitive PPA and RSC.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been hypothesized that neural states should reflect meaningful units in the environment (Baldassano et al, 2017). However up to now, neural state boundaries have only been linked to event boundaries specifically (Baldassano et al, 2017; Geerligs et al, 2022; Mariola et al, 2022) and it has not been investigated if neural states at different levels of the temporal hierarchy indeed represent different meaningful units. In line with this hypothesis, we found that there is a significant alignment between changes in location and neural state boundaries in the place-sensitive PPA and RSC.…”
Section: Discussionmentioning
confidence: 99%
“…One could wonder if the neural patterns observed in the fMRI scanners in response to watching movies could be a faithful representation of the activations that occur over real-life event transitions. The practice of using movies for event segmentation studies then leads to a circular inference, illustrated by exploring the ability to segment scenes even though the events are already explicitly "given" to the participants (Mariola et al, 2022).…”
Section: Studiesmentioning
confidence: 99%
“…An effective process of event segmentation is beneficial to individuals' understanding and memory of continuous information (Flores et al, 2017;Zacks et al, 2009). Event segmentation is based on top-down conceptual factors (e.g., comprehenders' goal, perspective, context knowledge or attentional focus) and bottom-up sensory factors (e.g., perceptual change of the object in narrative situation) (Bestgen & Vonk, 2000;Mariola et al, 2022;Zacks & Swallow, 2007). For example, comprehends will segment continuous narrative information in a storybook or film into discrete units based on their orientated attention to the perceptual change occurred in the aspects of character, space or time in the narrative (Bailey et al, 2017;Zacks et al, 2009).…”
Section: Introductionmentioning
confidence: 99%